A new species of the genus Paraphyllina (Scyphozoa: Coronatae): Paraphyllina kubanci sp. nov. from the Sea of Marmara, Turkey - Artüz, M. Levent (Zootaxa, 2023)
On August 9, 2008, during the MAREM (Marmara Environmental Monitoring) project survey, a single specimen of an unknown Scyphozoa was caught with a deep-water vertical plankton haul, below the thermo-halocline interface, at maximum 1042 m hauling depth, in the Sea of Marmara (40°44'00″N, 08°00'03″E), Turkey. In the following years, 22 specimens, which ranged in diameter from 18 to 26 mm and had the same characteristics, were caught in the same water mass of the Sea of Marmara during MAREM monitoring surveys. The specimens seem to correspond most closely with the medusae described by Maas (1903), Neppi (1915), and Russell (1956). All these specimens were similar in their essential characteristics, but differed in some details. Likewise, Paraphyllina kubanci sp. nov. differs from other species of the genus in terms of some characteristics, especially in the S-shaped gonads and in the distribution of coloration. It is identified as a new species of the genus Paraphyllina and described here.